2014
DOI: 10.1158/1055-9965.epi-14-0038
|View full text |Cite
|
Sign up to set email alerts
|

One-Carbon Metabolism Dietary Factors and Distal Gastric Cancer Risk in Chinese Women

Abstract: Background Previous studies on the association between one-carbon dietary factors and gastric cancer risk have been inconsistent. Methods We investigated this association using data from a prospective study, the Shanghai Women’s Health Study (1997–2010), including 323 distal gastric cancer cases identified from 73,009 Chinese women. Hazard ratios and 95% confidence intervals were estimated using Cox proportional hazard regression after adjusting for confounders. Results Overall, no statistically significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 60 publications
2
8
0
Order By: Relevance
“…Recent studies have reported the relationships between riboflavin status and some diseases such as certain types of cancers [ 12 , 13 , 14 , 15 , 16 ] and cardiovascular disease [ 18 ]. Riboflavin is involved in the folate-mediated one-carbon.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have reported the relationships between riboflavin status and some diseases such as certain types of cancers [ 12 , 13 , 14 , 15 , 16 ] and cardiovascular disease [ 18 ]. Riboflavin is involved in the folate-mediated one-carbon.…”
Section: Discussionmentioning
confidence: 99%
“…A high prevalence of inadequate riboflavin intake and status has been reported in various population groups in many countries including USA, UK, France, Poland, and Japan [ 8 , 9 , 10 , 11 ]. Also, the recent studies have indicated that riboflavin deficiency increases risk of cancer at certain sites; lung, distal stomach, esophagus, and rectum [ 12 , 13 , 14 , 15 , 16 ]. Some epidemiological studies have identified relationships between cardiovascular diseases and diets low in riboflavin [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The homocysteine score was modestly positively associated with the plasma homocysteine concentration (Pearson correlation coefficient r = 0.26 in the training set and 0.30 in the testing set, P # 0.001); positive correlation was consistently observed when homocysteine score and homocysteine concentration were compared in the study population combining both training and testing sets (n = 2023) (Supplemental Table 2). When comparing participants within the higher quartiles of the homocysteine score to those within the lowest quartile, there 5 Nutrient values are energy-adjusted intake. 6 We included dietary folate and supplementary folate separately in the model because of differential bioavailability between the 2 sources of folate.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, epigenetics incorporates inheritable as well as reversible phenomena that affect gene expression and stability without a change in the DNA base pairs (3). Potential disruption of metabolism due to an insufficient supply of relevant nutrients and imbalance of relevant dietary factors has been associated with cancer (4)(5)(6) and other health conditions (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…Until now, most studies of B vitamins and cancer prevention have focused on dietary intake estimates and risk of breast, prostate and colorectal cancers 3 , but serum B vitamin concentrations have previously also been measured mainly in studies of lung and colorectal cancers 1 4 . Only a few studies have explored the association between the intake of B vitamins and risk of oesophageal or gastric cancer 5 6 7 . In an intervention trial conducted in a northern county in China (Cixian), riboflavin-fortified salt was found to reduce the incidence of oesophageal squamous cell carcinoma (OSCC) 8 .…”
mentioning
confidence: 99%